Gene duplications in the TL region of the mouse major histocompatibility complex. - Hammerling, U (1985)
We have isolated a class I gene from the TL region of the A/J mouse. The gene, T2A, is a homologue of the C57BL/10 mouse gene T2. In the process of mapping this gene we screened a number of BALB/c class I cosmid clusters with a T2A flanking probe. Several of the hybridizing clusters were found to contain identical DNA segments and could therefore be linked together into one single BALB/c TL region which appears to be identical to the TL region of the C57BL/10 mouse. However, two of the hybridizing clusters do not overlap with the C57BL/10 TL region. It appears that these two clusters represent a partial duplication of the TL region in the BALB/c mouse.